Factors associated with tuberculosis disease in children from a hospital in Western Mexico - Juan C. Lona-Reyes; Jalil González-Valadez; Hugo C. Suárez Maytorena; Patricia Paredes-Casillas; Araceli Cordero-Zamora; Alfonso López-Godínez; Larissa M. Gómez-Ruiz (Permanyer, 2023)
Background: This study aimed to describe the clinical and demographic characteristics of children with confirmed tuberculosis disease and identify associated factors. Methods: We conducted a retrospective and observational study at the Hospital Civil de Guadalajara Dr. Juan I. Menchaca. Inpatient and outpatient children under 18 years of age who were reported to the National Epidemiological Surveillance System (SINAVE, for its Spanish acronym) for suspected tuberculosis and who had molecular or microbiological tests for mycobacteria were included in the study. Multivariate analysis with logistic regression was used to analyze associated factors. Results: One hundred and nine patients under 18 years of age with suspected tuberculosis were included in the study. About 50.5% (55/109) were male, and the median age was 11 years. Tuberculosis was confirmed in 55% (n = 60): 15% (9/60) had a pulmonary infection, and the rest (51/60) had an extrapulmonary infection. The diagnostic tests used were histopathological study (n = 26), expectoration or gastric aspirate stains (n = 17), polymerase chain reaction (n = 12), and cultures (n = 5). Positive purified protein derivative (PPD) or interferon- gamma release assay (IGRA) tests were found in 33.9%. Malnutrition (odds ratio [OR] 15.9, 95% confidence interval [CI]: 2.3-109), and consumption of unpasteurized products (OR 7.45, 95% CI: 1.02-54.3) were associated with tuberculosis disease in children. Conclusions: Malnutrition and consumption of unpasteurized dairy products are associated with tuberculosis.